Design and Optimization of Circularly Polarized Dual Band Patch Antenna Using Whale Optimization Algorithm for Wireless Communications - N. Nirmal Singh; K. Komathy Vanitha; M. S. Sumi; Jarin Joe Rini J; T. Geetha; Sundar Ramakrishnan (Buletin Ilmiah Sarjana Teknik Elektro, 2026)
In the realm of wireless communication systems, the demand for high-performance antennas proficient of accommodating numerous frequency bands whereas sustaining circular polarization has seen substantial growth. This work presents a unique approach for addressing this need. The antenna design begins with the incorporation of a patch structure, which, when properly configured, operates at 2.4GHZ and 5 GHz that corresponds to Wi-Fi bonds while simultaneously generating circular polarization. To optimize the antenna's performance, the Whale Optimization Algorithm (WOA) is employed. The WOA is a metaheuristic optimization approach enthused by the foraging behavior of humpback whales' feeding habits, known for its capability to proficiently explore complex solution spaces and find near-optimal configurations. This research emphasizes the importance of circular polarization in various wireless communication applications, comprising RFID systems, satellite communication, and GNSS receivers, among others. The utilization of dual bands ensures flexibility in accommodating multiple wireless standards within a single device. By leveraging the WOA, the antenna's parameters, such as dimensions and feeding techniques, are fine-tuned to maximize its circular polarization and impedance matching capabilities. This study's findings show how effective the suggested strategy is, showcasing a gain and return loss of 2.6353 dBi and -4.58 dB with radiation efficiency is 79.05 % at 2.4 GHZ and 74.83 % at 5 GHZ. Performance metrics, including gain, axial ratio, and impedance bandwidth, are rigorously evaluated, highlighting the antenna's suitability for contemporary wireless systems via wireless methods. Besides antenna design, this research offers plenty of benefits, as the integration of the WOA holds promise for enhancing the performance of other complex engineering systems.